Learning Outcomes on Intercultural Competence among Indonesian Exchange Students - Rafiqi, Fathan; Maksum, Ali (Newinera Publisher, 2025)
This study explores the development of intercultural competence (ICC) among Indonesian exchange students in South Korea and the United States, focusing on their experiences of cultural adaptation and the development of key intercultural skills. Employing a qualitative research design, the study utilized semi-structured interviews with 20 Indonesian students to investigate how they navigated cultural differences and adapted to new environments. The results identify three key dimensions of ICC: emotional sensitivity, cultural awareness, and intercultural adaptability. Emotional sensitivity was crucial for managing culture shock and emotional adaptation to the host culture. Cultural awareness, which involved recognizing and understanding cultural differences, enabled students to adjust their perceptions and behaviors. Intercultural adaptability, the ability to modify communication styles and social practices, was essential for effective engagement in both academic and social settings. The study contributes to the existing body of literature on international student experiences by providing insights into the specific challenges faced by Indonesian students and offering practical recommendations for improving support systems to foster intercultural competence. The findings highlight the dynamic nature of ICC as a process that evolves through emotional, cognitive, and behavioral adjustments. Future research should focus on the long-term impacts of intercultural experiences on students' personal and professional lives, as well as the role of cultural contexts in shaping ICC development.